Generation of nanocellular foams from ABS terpolymers. (April 2015) - Forest, C.; Chaumont, P.; Cassagnau, P.; Swoboda, B.; Sonntag, P.
Graphical abstract: Highlights: Foams of ABS copolymers have been produced using a gaseous CO2 process. A nanofoam with a double structures has been observed. Initial microstructures of ABS samples and foaming temperatures have a strong influence on the foam morphology. Abstract: ABS nano-cellular foams have been produced using a gaseous CO2 foaming process. ABS materials have been investigated in this study because of their specific morphologies, which can increase the nuclei density by creating heterogeneous nucleation near the interfaces between acrylonitrile–styrene and butadiene phases during the foaming process. This study focuses on the foaming of different ABS materials with a batch process using gaseous CO2 and presents the influence of the initial microstructures of ABS materials on their final foam structures. In specific cases, depending on initial ABS microstructures and also on foaming conditions, nano-cellular materials have been produced with foam double structures and effective porosity with 100 nm diameter open cells.